1995
DOI: 10.1111/j.1365-2311.1995.tb00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of competing species of seaweed flies: the role of temperature

Abstract: 1. Competition is shown to be occurring within and between the congeners Coelopa frigida and C.pilipes; it is noted that the two species frequently coexist despite ongoing competition.2. Observations on natural wrack-beds indicate that there is a marked difference in the distributions of the larvae: C.frigida larvae aggregate in cooler parts of the bed, C.pilipes in warmer parts. This difference in microdistribution reflects a broader-scale difference in the geographical distributions of the species -C.pilipes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…For instance, the case depicted in ¢gure 2b (solid lines) shows the possibility of two stable parasitic interactions, with the peculiarity that each species can play both the victim and exploiter roles interchangeably. Could this be the situation found by Phillips et al (1995) in the C. frigida and C. pilipes association? Figure 3 provides a situation where both competition and parasitism are feasible under identical or under di¡erent environments.…”
Section: (B) Matching Ecology and Modelsmentioning
confidence: 87%
“…For instance, the case depicted in ¢gure 2b (solid lines) shows the possibility of two stable parasitic interactions, with the peculiarity that each species can play both the victim and exploiter roles interchangeably. Could this be the situation found by Phillips et al (1995) in the C. frigida and C. pilipes association? Figure 3 provides a situation where both competition and parasitism are feasible under identical or under di¡erent environments.…”
Section: (B) Matching Ecology and Modelsmentioning
confidence: 87%
“…For example, leguminous or mycorrhizal plants benefit their neighboring plants by providing nitrogen or minerals and thus increase plant diversity or primary production (Bergelson, 1988;Bertness and Leonard, 1997;Díaz and Cabido, 2001;Fridley, 2001;Loreau et al, 2001;Tilman et al, 2001). Interaction between two seaweed flies, Coelopa frigida and C. pilipes, can change between acting as competitors or as amensalists (Phillips et al, 1995). As shown in Fig.…”
Section: Non-monotonicity Between Speciesmentioning
confidence: 99%
“…A previous investigation into the interactions between the two species of coelopid examined here (Phillips et al 1995a) suggested that C. pilipes could inhibit C.frigida under certain conditions. Although their finding appears to disagree with the facilitation found in this investigation, there were a number of differences between the two studies, the most obvious being that Phillips study?…”
Section: This Did Not Produce An Obvious Reversal Of Direct Effects mentioning
confidence: 63%
“…Adult flies were removed from each wrack sample by placing the whole sample in a bucket of concentrated saline and capturing the animals as they floated to the surface (Lavoie 1985;Phillips et al 1995a). Adult flies were removed from each wrack sample by placing the whole sample in a bucket of concentrated saline and capturing the animals as they floated to the surface (Lavoie 1985;Phillips et al 1995a).…”
Section: Colonizationmentioning
confidence: 99%
See 1 more Smart Citation